تحديد شروط وعوائق التعاون بين الممرض والطبيب من وجهة نظر الكادر التمريضي - طويل, علاء (Latakia University Journal -Medical Sciences Series, 2019)
The study aimed to identify the conditions and obstacles of collaboration between nurse and physician in the departments of ambulance and intensive care at Tishreen University Hospital and the National Hospital from the point of view of nursing staff. The sample consisted of 72 nurses from both hospitals (42 nurses from Tishreen Hospital and 30 nurses from the National Hospital), who were presented during the data collection and agreed to participate in the study (applied convenience sample). The researcher used a tool (questionnaire) for the conditions and obstacles of collaboration between nurse and physician for Adam & Osborne (1997), which consists of (6) items to define the conditions of collaboration and (10) items to identify the obstacles of collaboration between nurse and physician from the point of view of nursing staff. After the data collection, the data were released and analyzed using SPSS version 20. The most important results of the research were: The most conditions that must be met to achieve collaboration between nurse and physician from the point of view of nursing staff are in order: maturity in thinking, followed by work experience, support head of the department for collaboration between nurse and physician, and then respect physicians and nurses for the skills of each individual , Most recently supporting the hospital policy of collaboration between nurse and physician. And the obstacles of collaboration between nurse and physician from the point of view of nursing staff are in order: lack of continuous communication between nurses and physicians, and then the unequal influence between nurses and physicians, followed by the educational difference, and the absence of continuous meetings between them to discuss the work, , Lack of mutual trust between nurses and physicians, lack of respect for experience, lack of shared responsibilities, lack of respect or appreciation of information among nurses and physicians, and, finally, lack of time to discuss patients among physicians and nurses. هدف البحث إلى تحديد شروط وعوائق التعاون بين الممرض والطبيب في أقسام الإسعاف والعناية المشددة في مشفى تشرين الجامعي والمشفى الوطني من وجهة نظر الكادر التمريضي. تكونت العينة من72 ممرض وممرضة من كلا المشفيين (42 ممرض/ة من مشفى تشرين الجامعي و30 ممرض/ة من المشفى الوطني), ممن تواجدوا أثناء جمع البيانات ووافقوا على المشاركة في الدراسة (طبقت العينة المتاحة). استخدم الباحث أداة (استبيان) شروط وعوائق التعاون بين الممرض والطبيب لـ Adam & Osborne (1997) الذي تكون من (6) عبارات لتحديد شروط التعاون و (10) عبارات لتحديد عوائق التعاون بين الممرض والطبيب من وجهة نظر الكادر التمريضي واستخدم مقياس ليكرت الخماسي. وبعد جمع البيانات, تم تفريغ البيانات و تحليلها باستخدام أساليب و برامج إحصائية متخصصة SPSS النسخة 20. أهم النتائج التي توصل إليها البحث: أنّ أكثر الشروط التي يجب توفرها لتحقيق التعاون بين الممرض والطبيب من وجهة نظر الكادر التمريضي هي بالترتيب: النضج في التفكير, يليه الخبرة في العمل, دعم رئيس القسم للتعاون بين الممرض والطبيب, ومن ثمّ احترام الأطباء والممرضين لمهارات كل فرد, وآخرها دعم سياسة المشفى للتعاون بين الممرض والطبيب. وأنّ عوائق التعاون بين الممرض والطبيب من وجهة نظر الكادر التمريضي هي بالترتيب: عدم التواصل المستمر بين الممرضين والأطباء, ومن ثمّ عدم التساوي في النفوذ بين الممرضين والأطباء, ويليهما الفارق التعليمي, وعدم وجود اجتماعات مستمرة بينهم لمناقشة العمل, وكذلك عدم وجود المكان المناسب لعقد الاجتماعات, ومن ثمّ عدم وجود ثقة متبادلة بين الممرضين والأطباء, وعدم وجود احترام للخبرة وعدم وجود تشارك في المسؤوليات, ثم عدم وجود احترام أو تقدير لمعلومات كل فرد بين الممرضين والأطباء, وأخيراً عدم توفر الوقت الكافي لمناقشة حالة المرضى بين الأطباء والممرضين.